The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1136/bmjspcare-2012-000196.171
|View full text |Cite
|
Sign up to set email alerts
|

Electronic palliative care co-ordination systems improve information provided to out of hours teams

Abstract: The UK Department of Health (DOH) End-of-life care strategy advocates Electronic Palliative Care Coordination Systems (EPCCS) to improve communication across providers in acute and community sectors 24 h a day. The Royal Marsden NHS Foundation Trust was an EPCCS pilot site. This audit compares the information available to the London Ambulance Service (LAS) on the EPCCS to the information previously provided by a faxed paper form. Aim To determine if the EPCCS improved the quality of the information shared. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Overall, the data quality of information on CMC has improved compared with the audit of 2010 faxed handover information to London Ambulance 14. However, this report highlights areas for improvement pertaining to the design and set up of the IT used to store the CMC records.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Overall, the data quality of information on CMC has improved compared with the audit of 2010 faxed handover information to London Ambulance 14. However, this report highlights areas for improvement pertaining to the design and set up of the IT used to store the CMC records.…”
Section: Discussionmentioning
confidence: 96%
“…In 2010, an audit of 154 faxed handover forms14 sent to the LAS showed that 112 (72.7%) forms had the consent questions answered. The answer to ‘Do you have the consent of the patient for the transfer of information?’ was ‘no’ in 36 (32%).…”
Section: Discussionmentioning
confidence: 99%